National cohort study on postoperative risks after surgery for submucosal invasive colorectal cancer. Issue 2 (24th December 2018) - Vermeer, N. C. A.; Backes, Y.; Snijders, H. S.; Bastiaannet, E.; Liefers, G. J.; Moons, L. M. G.; van de Velde, C. J. H.; Peeters, K. C. M. J.
Abstract : Background: The decision to perform surgery for patients with T1 colorectal cancer hinges on the estimated risk of lymph node metastasis, residual tumour and risks of surgery. The aim of this observational study was to compare surgical outcomes for T1 colorectal cancer with those for more advanced colorectal cancer. Methods: This was a population‐based cohort study of patients treated surgically for pT1–3 colorectal cancer between 2009 and 2016, using data from the Dutch ColoRectal Audit. Postoperative complications (overall, surgical, severe complications and mortality) were compared using multivariable logistic regression. A risk stratification table was developed based on factors independently associated with severe complications (reintervention and/or mortality) after elective surgery. Results: Of 39 813 patients, 5170 had pT1 colorectal cancer. No statistically significant differences were observed between patients with pT1 and pT2–3 disease in the rate of severe complications (8·3 versus 9·5 per cent respectively; odds ratio (OR) 0·89, 95 per cent c.i. 0·80 to 1·01, P = 0·061), surgical complications (12·6 versus 13·5 per cent; OR 0·93, 0·84 to 1·02, P = 0·119) or mortality (1·7 versus 2·5 per cent; OR 0·94, 0·74 to 1·19, P = 0·604). Male sex, higher ASA grade, previous abdominal surgery, open approach and type of procedure were associated with a higher severe complication rate in patients with pT1 colorectal cancer. Conclusion: Elective bowel resection was associated with similar morbidity and mortality rates in patients with pT1 and those with pT2–3 colorectal carcinoma. Abstract : Clinicians should be aware that the risks associated with elective bowel resection for pT1 colorectal cancer are similar to those for elective surgery in more advanced colorectal cancer. The risk stratification table provided in this study might help to estimate the risk for individual patients, thereby enhancing shared decision‐making. Complications after surgery for T1 colorectal carcinoma